Development and Characterization of Gastroretentive Drug Delivery System of Olmesartan Medxomil (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The objective of the study was to develop an optimized gastro retentive drug delivery system of Olmesartan Medoxomil. The tablets were formulated by direct compression using HPMC K15M, HPMC K4M, Xanthan Gum and PVP K30. Sodium bicarbonate was used as the gas generating agent to reduce the floating lag time. The drug-polymer interaction was evaluated by Fourier Transform Infrared Spectroscopy (FTIR) and DSC study. The FTIR and DSC study indicated the lack of drug-polymer interaction. The formulated tablets were evaluated for hardness, weight variation, thickness, floating capacity, swelling index, drug content, in vitro dissolution study. Formulations were following nonfickian (anamalous) diffusion as the release mechanism from all the floating tablets prepared with various polymers.